Safety and efficacy of Viva QS® for smoking cessation among industrial workers in Kerteh and Kuantan, Malaysia - Mohamad Noor, Zaswiza; Md Aris, Mohd Aznan; Nik Mohamed, Mohamad Haniki; Draman, Samsul; Shaikh Rahman Bux, Siti Halimah Bux (Japan International Cultural Exchange Foundation (JICEF), 2011)
Objective: To evaluate the safety and efficacy of Viva QS®, an herbal medication consists of a combination of twelve herbs for smoking cessation in Malaysian adult smokers. Methods: A randomized, double-blind placebo-controlled study was conducted in the industrial factories in Kerteh and Kuantan, Malaysia. The subjects were recruited from those attended mobile smoking cessation programme (MSCP), agreed to sign written consent and fulfilled study criteria. Demographic and smoking history information, modified Fagerström test for nicotine dependence (FTND) score and carbon monoxide (CO) level were obtained at baseline. Follow-up were conducted by phone calls and/or face-to-face meetings at three time points. Viva QS® and placebo were supplied for 24 weeks. Results: One hundred and fifty-five subjects were randomized from 1st April 2008 to 26th October 2008 in the study. Biochemically verified 7-days point prevalence demonstrated Viva QS® significantly increased quit rate vs. placebo; 42.7% vs. 26.2% (p = 0.038) at week 4, 32.0% vs. 16.7% (p = 0.031) at week 12 and 30.7% vs. 13.9% (p = 0.015) at week 24. Adverse events reported were similar between groups. The most frequently reported adverse events were sore throat and dry mouth (36.6% and 17.8%, respectively for Viva QS® vs. 28.8% and 16.9% for placebo). Conclusions: Viva QS is safe and effective to aid smokers quit smoking in this population sample.